Evaluation And Analysing Causes Of Patients Presenting With Chronic Headache At A Tertiary Care Centre - Shah, Siddharth; Chaudhary, Arvind; Darda, Shubham; Mehta, Chiranjeev; Kaneria, Shivam (Journal of Neonatal Surgery, 2025)
Chronic headaches are regarded by the WHO as one of the common incapacitating disorders. The purpose of this study was to determine the clinical characteristics, assessment, and frequency of subtypes of primary chronic headache. Methodology: The study was conducted at Dhiraj Hospital in Vadodara, Gujarat. The research, which had patients aged 18 and older who had main persistent headaches that could not be attributed to any organic cause, was questionnaire-based and completed by the investigator. An episode of a chronic headache was defined in this study as one that persisted for at least three consecutive months and for at least 15 days. Relevant examination and CT/MRI ruled out secondary reasons. Results: The most prevalent kind of chronic primary headache among the 150 patients was migraine (52%), with CTTH occurring in 33.33%, hemicrania in 7.33%, and NDPH in 7.33%. Women and younger age groups had a much higher prevalence of chronic headaches. Conclusion: Headaches are considered to be equally dangerous as any other neurological disorder in India. Migraine produces a great deal of disability, which includes a heavy load on family life and forced absences from work.